Community intervention: assessment of parental training of a family prevention programme of substance use and associated risk behaviours - São Martinho, Sofia (Pontificia Universidad Javeriana, 2017)
El manuscrito presenta los resultados de un proyecto familiar de intervención comunitaria de prevención del consumo de drogas. El proyecto se basa en dos modelos de integración - Modelo Estructural de Cowen y Modelo Eco-Desarrollo, adoptando una perspectiva multicausal y guiándose por el principio metodológico de empoderamiento. Este estudio tuvo dos momentos de evaluación: (T1) una semana antes de la intervención y (T2) una semana después del final de la intervención. Se presentan los datos reunidos de 42 adultos con responsabilidades parentales y los resultados indican cambios significativos a nivel familiar en el aumento de la cohesión, expresividad, el control y en el aumento de la orientación de las actividades recreativas. También se observa una disminución de las estrategias educativas que caracterizan los estilos autoritarios y permisivos. Abstract The manuscript presents the results of a family and community intervention project to prevent drug use. The project was theoretically based in two integrative models - Structural Model of Cowen and Eco-Developmental Model and has taken a multicausal perspective and the methodological principle of empowerment. This study had two assessment moments: (T1) a week before the intervention and (T2) a week after the end of the intervention. Data collected from 42 adults with parenting responsibilities and the results indicate significant changes in the increase of cohesion, expressivity, control and the increase of the orientation for recreational activities. It is also observed a decrease of the educational strategies that characterise the authoritarian and permissive styles.